Defect management method for content-based document artifact test in software R&D project - Baek, Dusan; Shin, Jong Hwan; Lee, Byungjeong; Lee, Jung Won (Lecture Notes in Electrical Engineering, 2018)
In order to improve the quality of software R&D project, studies on the content-based document artifact test (CbDAT), which considers the heterogeneity of the research phase compared to development phase, have been introduced. The CbDAT manages the research phase by testing the document artifacts which could not be performed by the conventional software test. However, the existing studies on the CbDAT have a limitation in managing because they only consider test planning and test execution. To solve this problem, we analyze the characteristics of the CbDAT and derive six major differences. Based on these, we propose activities that researchers should perform for the defect management. In addition, we present an incident report and defect severity reflecting the characteristics of the CbDAT. The defect management method proposed in this paper enables the researcher to manage defects identified from the CbDAT and to improve the quality of software R&D project.
Keywords: Compliance; Content-based; Defect management; Development phase; Guideline; Incident reports; Quality of softwares; Test execution; Compliance; Content-based document artifacts test; Defect management; Guideline; Software document